Raising the ‘Good’ Oxidants for Immune Protection - Dumas, Alexia; Knaus, Ulla G. (Frontiers in Immunology, 2021)
Redox medicine is a new therapeutic concept targeting reactive oxygen species (ROS) and secondary reaction products for health benefit. The concomitant function of ROS as intracellular second messengers and extracellular mediators governing physiological redox signaling, and as damaging radicals instigating or perpetuating various pathophysiological conditions will require selective strategies for therapeutic intervention. In addition, the reactivity and quantity of the oxidant species generated, its source and cellular location in a defined disease context need to be considered to achieve the desired outcome. In inflammatory diseases associated with oxidative damage and tissue injury, ROS source specific inhibitors may provide more benefit than generalized removal of ROS. Contemporary approaches in immunity will also include the preservation or even elevation of certain oxygen metabolites to restore or improve ROS driven physiological functions including more effective redox signaling and cell-microenvironment communication, and to induce mucosal barrier integrity, eubiosis and repair processes. Increasing oxidants by host-directed immunomodulation or by exogenous supplementation seems especially promising for improving host defense. Here, we summarize examples of beneficial ROS in immune homeostasis, infection, and acute inflammatory disease, and address emerging therapeutic strategies for ROS augmentation to induce and strengthen protective host immunity.